HUBUNGAN FAKTOR RISIKO IBU HAMIL DENGAN KADAR GULA DARAH DI DESA OLILIT TAHUN 2025 - Saragih, Kristiova Masnita; Magdalena Sitorus, Sony Bernike (Jurnal Kebidanan, 2025)
IDF (International Diabetes Federation) stated that around 21.1 million (16.7%) live births to women in 2021 experienced hyperglycemia in certain pregnancies. Of these, 80.3% were caused by gestational diabetes mellitus (GDM), while 10.6% were caused by diabetes detected before pregnancy, and 9.1% were caused by diabetes (including type 1 and type 2) first detected in pregnancy. The purpose of this study was to determine the relationship between risk factors for pregnant women and blood sugar levels in Olilit village, Tanmbar Islands district. This research method is a quantitative descriptive study with a type of research is Cross Sectional using a questionnaire. The population of this study were all pregnant women who checked their pregnancy at the Olilit village Posyandu. The sample of this study was pregnant women who underwent ANC examinations, laboratory examinations of blood sugar levels 2 hours after eating >140 mg/dl in Olilit village, for the period January - April 2025, as many as 47 pregnant women. There are 21 pregnant women with abnormal blood sugar levels (44.68%), the majority are aged 21-35 years (9 people) (42.86%), 3rd trimester pregnancy age, 11 people (53.38%), have a family history of diabetes mellitus (5 people) (23.81%), abnormal blood pressure (12 people) (57.14%) Based on the results of bivariate analysis, the age and blood pressure of pregnant women have a relationship with blood sugar levels (p <0.001) in Olilit village. For that, every pregnant woman who checks her pregnancy, needs to have a blood sugar level check and counseling about gestational diabetes as an early detection of the dangers of diabetes in pregnancy Keyword: risk factors for pregnant women, blood sugar levels